Perioperative Risk Factors for Intraoperative Hypothermia in Adult Patients Undergoing Elective Surgery at Jigme Dorji Wangchuk National Referral Hospital, Bhutan : a Prospective Observational Study - Kinley Zangmo (Prince of Songkla University, 2021)
Thesis (M.Sc. (Health Sciences))--Prince of Songkla University, 2019